The Effect of Capital Intensity, Audit Quality, Thin Capitalization, and Gender Diversity on Tax Aggressiveness - Yoga Adi Pratama; Muhammad Abdul Aris (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effects of capital intensity, audit quality, thin capitalization, and gender diversity on tax aggressiveness in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. This research adopts a quantitative approach with an associative method, and the sample is selected using purposive sampling based on criteria such as SOEs listed on IDX, financial reports expressed in Indonesian Rupiah, and excluding the banking sector. The dependent variable is tax aggressiveness, measured using the Effective Tax Rate (ETR), while the independent variables are capital intensity, audit quality, thin capitalization, and gender diversity. Data analysis is performed using multiple linear regression and classical assumption tests to ensure the validity of the regression model. The findings indicate that capital intensity, audit quality, thin capitalization, and gender diversity significantly affect tax aggressiveness. This research has limitations, such as the restriction to SOEs and a three-year observation period. Future research is suggested to expand the scope by using the IDX-IC classification and extending the study period, as well as considering additional variables such as firm size and ownership structure.